Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/ptr.6695
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharide from Pycnoporus sanguineus ameliorates dextran sulfate sodium‐induced colitis via helper T cells repertoire modulation and autophagy suppression

Abstract: Inflammatory bowel disease (IBD) is a chronic autoimmune disease associated with various risk factors. Pycnoporus sanguineus (L.) Murrill is a saprotrophic fungus used worldwide for its industrial and medical purposes. Here, polysaccharide from P. sanguineus (PPS) was explored for its antiinflammatory potential in a murine colitis model of IBD induced by dextran sulfate sodium (DSS). PPS ameliorated the colitis as manifested by the lowered disease activity index (DAI), prolonged colon, and reduced serum lipopo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 60 publications
1
5
0
Order By: Relevance
“…Although our previous results suggested that SETD8 plays an important role in inflammatory process, the underlying mechanism remains unclear. In consistent with some previous studies, 22,23 using a public dataset of UC and CD patients, we identified that p62 was upregulated in IBD patients, and our western blot analysis confirmed the result (Fig. 5a,b).…”
Section: Setd8 Involved In Intestinal Inflammation Via Regulating P62supporting
confidence: 92%
See 1 more Smart Citation
“…Although our previous results suggested that SETD8 plays an important role in inflammatory process, the underlying mechanism remains unclear. In consistent with some previous studies, 22,23 using a public dataset of UC and CD patients, we identified that p62 was upregulated in IBD patients, and our western blot analysis confirmed the result (Fig. 5a,b).…”
Section: Setd8 Involved In Intestinal Inflammation Via Regulating P62supporting
confidence: 92%
“…21 In particular, some studies reported that elevated protein level of p62 was observed in the colon mucosa of ulcerative colitis (UC) patients and DSS-induced colitis mice, accompanied with upregulated inflammatory cytokines. 22,23 Collectively, these observations suggested a pivotal role of p62 in inflammatory diseases.…”
Section: Introductionmentioning
confidence: 89%
“…P. sanguineus is a saprophytic fungus, which is widely applied in industry and medicine all over the world. Li M. X. et al (2020) extracted a polysaccharide PPS from P. sanguineus and found that PPS could alleviate the colitis induced by DSS, which is manifested by reducing DAI, colon shortening, colonic MPO activity, and serum LPS concentration. PPS could effectively restored intestinal barrier function by increasing the expression of ZO-1, E-cadherin, and PCNA.…”
Section: Polysaccharides From Mushroomsmentioning
confidence: 99%
“…As a scaffold protein, ZO‐1 can connect claudins, occludin, and cytoskeletal fibrin to form a stable tight junction complex. ZO‐1 protein expression is reduced in IBD, 21 suggesting impaired intestinal mucosal barrier function in IBD. TNF‐α, a key mediator of intestinal inflammation, has been shown to increase intestinal epithelial tight junction permeability 22 and induce apoptosis and inflammatory response in intestinal epithelial cells 23 .…”
Section: Discussionmentioning
confidence: 99%